2012
DOI: 10.1017/jfm.2011.534
|View full text |Cite
|
Sign up to set email alerts
|

Sinking, merging and stationary plumes in a coupled chemotaxis-fluid model: a high-resolution numerical approach

Abstract: Aquatic bacteria like Bacillus subtilis are heavier than water yet they are able to swim up an oxygen gradient and concentrate in a layer below the water surface, which will undergo Rayleigh-Taylor-type instabilities for sufficiently high concentrations. In the literature, a simplified chemotaxis-fluid system has been proposed as a model for bioconvection in modestly diluted cell suspensions. It couples a convective chemotaxis system for the oxygen-consuming and oxytactic bacteria with the incompressible Navie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

8
99
0
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 128 publications
(109 citation statements)
references
References 37 publications
8
99
0
1
Order By: Relevance
“…Accordingly, the literature on coupled chemotaxis-fluid systems is yet quite fragmentary, and beyond very interesting numerical findings [5,22], most rigorous analytical results available so far concentrate either on special cases involving somewhat restrictive assumptions, or on variants of (1.2) which contain additional regularizing effects. For instance, a considerable simplification consists in removing the convective term (u · ∇)u from the third equation in (1.2), thus assuming the fluid motion to be governed by the linear Stokes equations.…”
Section: Introductionmentioning
confidence: 99%
“…Accordingly, the literature on coupled chemotaxis-fluid systems is yet quite fragmentary, and beyond very interesting numerical findings [5,22], most rigorous analytical results available so far concentrate either on special cases involving somewhat restrictive assumptions, or on variants of (1.2) which contain additional regularizing effects. For instance, a considerable simplification consists in removing the convective term (u · ∇)u from the third equation in (1.2), thus assuming the fluid motion to be governed by the linear Stokes equations.…”
Section: Introductionmentioning
confidence: 99%
“…This assumption is less natural, at least for the part of the boundary that separates water and air, but so far has been employed in almost all papers dealing with chemotaxis fluid interaction from a mathematical viewpoint (exceptions being early existence results for weak solutions in 2-dimensional bounded domains [25], numerical experiments like in [6] and, most notably, a recent work by Braukhoff [4], where it was shown that in 2-or 3-dimensional convex bounded domains classical or weak solutions, respectively, exist for a chemotaxis-Navier-Stokes model with logistic source if the boundary condition for c is ∂ ν c = 1 − c). Thus, in total the system to be considered here is n t + u · ∇n = ∆n − χ∇ · (n∇c) + κn − µn …”
Section: Introductionmentioning
confidence: 99%
“…The function χ(c) describes the chemotactic sensitivity whereas f (c) is the consumption rate of the bacteria. The chemotaxis-fluid system has been studied in the past several years [2][3][4][5][6]9,20,22,31,32,37]. Lorz [21] showed local existence of weak solutions of (1.1) in a bounded domain in R d , d = 2, 3 with no-flux boundary condition and in R 2 in the case of inhomogeneous Dirichlet conditions for the oxygen.…”
Section: Introductionmentioning
confidence: 99%
“…6) under homogeneous boundary condition ∂n R ∂ν = ∂c R ∂ν and u R = 0, x ∈ ∂B R , t > 0, (1.7) and the initial data are chosen as…”
Section: Introductionmentioning
confidence: 99%